Replication by the Epistasis Project of the interaction between the genes for IL-6 and IL-10 in the risk of Alzheimer's disease - Combarros, Onofre (BioMed Central, 2009)
BACKGROUND: Chronic inflammation is a characteristic of Alzheimer's disease (AD). An interaction associated with the risk of AD has been reported between polymorphisms in the regulatory regions of the genes for the pro-inflammatory cytokine, interleukin-6 (IL-6, gene: IL6), and the anti-inflammatory cytokine, interleukin-10 (IL-10, gene: IL10). METHODS: We examined this interaction in the Epistasis Project, a collaboration of 7 AD research groups, contributing DNA samples from 1,757 cases of AD and 6,295 controls. RESULTS: We replicated the interaction. For IL6 rs2069837 AA × IL10 rs1800871 CC, the synergy factor (SF) was 1.63 (95% confidence interval: 1.10–2.41, p = 0.01), controlling for centre, age, gender and apolipoprotein E ε4 (APOEε4) genotype. Our results are consistent between North Europe (SF = 1.7, p = 0.03) and North Spain (SF = 2.0, p = 0.09). Further replication may require a meta-analysis. However, association due to linkage disequilibrium with other polymorphisms in the regulatory regions of these genes cannot be excluded. CONCLUSION: We suggest that dysregulation of both IL-6 and IL-10 in some elderly people, due in part to genetic variations in the two genes, contributes to the development of AD. Thus, inflammation facilitates the onset of sporadic AD.